2019
DOI: 10.15420/icr.2018.37.1
|View full text |Cite
|
Sign up to set email alerts
|

TAVI for Pure Native Aortic Regurgitation: Are We There Yet?

Abstract: Treatment of degenerative aortic stenosis has been transformed by transcatheter aortic valve implantation (TAVI) over the past 10–15 years. The success of various technologies has led operators to attempt to broaden the indications, and many patients with native valve aortic regurgitation have been treated ‘off label’ with similar techniques. However, the alterations in the structure of the valve complex in pure native aortic regurgitation are distinct to those in degenerative aortic stenosis, and there are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 52 publications
1
47
0
Order By: Relevance
“…These include valve-in-valve treatment for failing bio-prostheses, treatment of bicuspid aortic valves in younger patients with complex anatomical features, and for native pure AR; however, these techniques have not been evaluated in QAV. 21 Quadricuspid aortic valve can accentuate the risk of native valve endocarditis due to the supernumerary cusp. Consequently, antibiotic prophylaxis can be quite controversial with experts advocating both for and against strategies based on valve morphology and degree of AR.…”
Section: Discussionmentioning
confidence: 99%
“…These include valve-in-valve treatment for failing bio-prostheses, treatment of bicuspid aortic valves in younger patients with complex anatomical features, and for native pure AR; however, these techniques have not been evaluated in QAV. 21 Quadricuspid aortic valve can accentuate the risk of native valve endocarditis due to the supernumerary cusp. Consequently, antibiotic prophylaxis can be quite controversial with experts advocating both for and against strategies based on valve morphology and degree of AR.…”
Section: Discussionmentioning
confidence: 99%
“…15 The role of TAVR has been explored in the management of aortic regurgitation of both native and bioprosthetic valves. 16 In the setting of contemporary left ventricularÀassist devices, the risk of significant aortic regurgitation approaches 30% at 3 years. 17 Recent pilot trials have demonstrated the safety and efficacy of TAVR in this setting, offering a transcatheter solution to minimize aortic regurgitation and increase forward flow.…”
Section: Anesthetic Technique In Tavrmentioning
confidence: 99%
“…19 Points of consideration during the evolution of TAVR for aortic regurgitation include lack of annular calcification, reliance on echocardiographic imaging for positioning, the need for oversizing of the valve, and the risks of valve complications such malposition, migration, and aortic annular rupture. 16,19 Further trials will likely evaluate these considerations in the era of expanding indications for TAVR for aortic regurgitation and beyond.…”
Section: Anesthetic Technique In Tavrmentioning
confidence: 99%
“…Off-label TAVR in pure aortic regurgitation has to face important challenges like necessary oversizing for anchoring without calcium; the associated risk of dislocation, annular rupture, and PVL; as well as frequently observed too large anatomies for current available TAVR devices. However, TAVR is likely to be established as an applicable alternative treatment with new dedicated devices in time [50]. Figure 5 gives an overview on the diagnostics, challenges, and important considerations in the context of treatment allocation.…”
Section: Treatment Optionsmentioning
confidence: 99%